2021
DOI: 10.3389/fsufs.2021.641858
|View full text |Cite
|
Sign up to set email alerts
|

Kageneckia oblonga Leaves Subjected to Different Drying Methods: Drying Kinetics, Energy Consumption and Interesting Compounds

Abstract: In this study, Kageneckia oblonga leaves were dried under different drying conditions and techniques [oven drying (NC), vacuum drying (VNC), convective drying (FC), and microwave-assisted convective drying (MWFC)]. Thus, the effect of temperature, vacuum, and microwave on the drying features of K. oblonga leaves was determined. Fick's second law was used to calculate the effective moisture diffusivity that varied from 3.94 to 8.14 × 10−11 m2/s, 1.12 to 1.40 × 10−11 m2/s, 7.83 to 11.36 × 10−11 m2/s, and 6.93 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This is consistent with work by Calín-Sánchez et al [ 45 ]. Considering the data shown in Figure 2 and Table 3 , it can be concluded that with shorter time required to reduce moisture content to 5%, the energy consumption decreased, which is consistent with previous studies by Zambra et al [ 46 ] and Amado et al [ 47 ].…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with work by Calín-Sánchez et al [ 45 ]. Considering the data shown in Figure 2 and Table 3 , it can be concluded that with shorter time required to reduce moisture content to 5%, the energy consumption decreased, which is consistent with previous studies by Zambra et al [ 46 ] and Amado et al [ 47 ].…”
Section: Resultssupporting
confidence: 90%
“…At a higher temperature (70 • C), the relative change ranged from 36% (for CU) to 371% (for CMU). This aligns with earlier findings by Wiset et al [46] on cherry tomatoes, Md Salim et al [47] on broccoli stalks, and Zambra et al [43] on Kageneckia oblonga leaves.…”
Section: Drying Parameters and Specific Energy Consumptionsupporting
confidence: 92%
“…During this stage, the diffusion of moisture within the material primarily dictates the drying rate, which continually decreases throughout the drying process. This explains the low efficiency of convection drying and corroborates the findings of previous researchers [42][43][44]. The increase in the drying rate of the hybrid programs was highly dependent on the type of reinforcement used and the air temperature.…”
Section: Drying Parameters and Specific Energy Consumptionsupporting
confidence: 90%
“…As a result of the high MC of the leaves during the early drying stage, increased microwave power absorption led to higher DR because more moisture was diffused to the surface. As the amount of MC in the leaves gradually diminishes, less microwave energy is absorbed, which causes the DR to fall (Zambra et al, 2021). Figure 2 shows that the DR decreases sharply as the microwave power increases.…”
Section: Resultsmentioning
confidence: 99%